Available resources and inclusive practices for students with special educational needs: perceptions of Brazilian and Portuguese teachers - Rodrigues, Olga Maria Piazentin Rolim; Santos, Camila Elidia Messias dos; Vieira, Susana Maria Veiga de Sousa; Grande, Catarina; Alves, Diana (Frontiers in Education, 2026)
Inclusive resources can contribute to the development of inclusive teaching practices and equity in education. The study aimed to analyze the perception of Brazilian and Portuguese teachers who work with students with special educational needs regarding the inclusive resources available and their inclusive practices, correlating them with personal variables (age, gender) and professional variables (teaching experience, education cycle in which they work, and participation in Special and Inclusive Education courses). A total of 85 Brazilian and 94 Portuguese teachers from public basic education schools participated in the study. The majority were women, with a mean age of 43.6 years among Brazilian teachers and 54.5 years among Portuguese teachers. For most Brazilian teachers, teaching experience was under 20 years, whereas for Portuguese teachers, it was over 20 years. Brazilian teachers predominantly worked in Early Childhood Education and Elementary School I, while Portuguese teachers mainly worked in the third cycle of basic education. Regarding training, 70% of Brazilian teachers and 42% of Portuguese teachers had completed courses in Special and Inclusive Education or related areas. Data collection employed a sociodemographic questionnaire and the Resources and Practices for Inclusive Education instrument, composed of 24 items: nine to assess available resources and 15 to assess inclusive practices in the classroom. Data were collected online. Results indicated that 80% of Portuguese teachers and 34% of Brazilian teachers agreed that resources for inclusion were available. Regarding inclusive practices, 98% of teachers from both countries reported using them in the classroom. Among Brazilian teachers, those with more students specific needs and those who had training in inclusive education perceived more available resources and reported better practices. Brazilian teachers with less experience and those teaching students with Autism Spectrum Disorder (ASD) and alongside students with other conditions perceived fewer available inclusive resources. Among Portuguese teachers, those who perceived more resources available reported more inclusive practices, and teachers who used additional measures exhibited higher levels of inclusive practices.